Towards Healthy Toddlers: The Role of Health Workers in the Prevention and Control of Malnutrition in Banjar Regency - rusmilawaty, rusmilawaty; Hapisah; Rafidah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
Aluh-aluh Besar Village is one of 22 villages located in the Aluh-aluh Subdistrict of Banjar Regency, South Kalimantan Province, consisting of 11 neighborhood associations with a relatively high prevalence of malnutrition among children aged 7-59 months, namely 49 children (34.7%) out of 141 children. The solution to address the issues in Aluh-aluh Besar Village is to conduct integrated training, provide guidance to Posyandu cadres and mothers of infants to enhance their knowledge and skills in detecting, preventing, and addressing malnutrition in infants, form infant nutrition support groups using social media (WA group), conduct continuous monitoring and evaluation, and collaborate between the village government, Aluh-aluh Health Center -Aluh Health Center to support the prevention and management of malnutrition. The method applied was to provide counseling and assistance to 20 mothers and 10 cadres. This activity involved mothers of toddlers, cadres, nutritionists, and 3 students. The final outcome of this community service activity is to enhance participants' knowledge and skills regarding infant nutrition, methods for determining nutritional status, and addressing malnutrition. A support group for infant nutrition was formed using social media (WhatsApp group) comprising mothers of infants and health workers to share knowledge, experiences, support, and useful information about toddler nutrition, and the establishment of cooperation between the local government in Aluh-aluh Besar Village and the Aluh-Aluh Health Center, as well as in supporting the malnutrition prevention program. The final evaluation in September 2025 showed a 5.75% decrease in malnourished toddlers.